2007
DOI: 10.1093/treephys/27.4.577
|View full text |Cite
|
Sign up to set email alerts
|

The ecological and functional correlates of nocturnal transpiration

Abstract: Contrary to the conventional theory of optimal stomatal control, there is substantial transpiration at night in many tree species, but the functional significance of this phenomenon remains uncertain. To investigate the possible roles of nocturnal transpiration, we compared and contrasted the correlations of both nocturnal and diurnal sap flow with a range of traits in 21 temperate deciduous tree species. These traits included soil water affinity, shade tolerance, cold hardiness, nitrogen concentration of tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 57 publications
6
75
0
1
Order By: Relevance
“…Such phenomenon can be explained by night transpiration, especially in the upper part of the crowns, since the stomata are partly open under non-saturated air conditions. This phenomenon has been reported in several studies (Dawson et al 2007), including on 3-year-old Fagus grandifolia (Marks and Lechowicz 2007) and on adult F. sylvatica (Seibt et al 2007;Samson et al 2003). During the period of strongest water stress (DOYs 200 to 235), when predawn water potential measurements were performed, the air was not saturated and air vapour pressure deficit was 5.6 hPa on average above the canopy.…”
Section: Stomata Opening During Night?supporting
confidence: 59%
“…Such phenomenon can be explained by night transpiration, especially in the upper part of the crowns, since the stomata are partly open under non-saturated air conditions. This phenomenon has been reported in several studies (Dawson et al 2007), including on 3-year-old Fagus grandifolia (Marks and Lechowicz 2007) and on adult F. sylvatica (Seibt et al 2007;Samson et al 2003). During the period of strongest water stress (DOYs 200 to 235), when predawn water potential measurements were performed, the air was not saturated and air vapour pressure deficit was 5.6 hPa on average above the canopy.…”
Section: Stomata Opening During Night?supporting
confidence: 59%
“…Marks and Lechowicz (2007) correlated higher sap flow with higher leaf nitrogen and dark respiration across 21 temperate tree species, suggesting that g night may have a role in dark respiration. However, in this study we found a negative relationship between g night and A in the 7 and 600 mM treatments (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…However, several benefits for night-time water loss have been proposed, including enhanced nutrient supply (Snyder et al 2008), prevention of excess cell turgor , and enhanced early morning carbon gain . Although any proposed benefits have yet to be quantified directly, several studies have used natural variation in g night both among and within species to develop adaptive hypotheses explaining the occurrence of high g night (Marks and Lechowicz 2007;Christman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although plants actively close their stomata in the dark, stomatal closure is largely incomplete and nighttime transpiration can be substantial, accounting for up to 30% of the plant's daytime water loss (15). Furthermore, variation in E n has been identified across (15)(16)(17) and within (15,(18)(19)(20) plant species, but little is known about the underlying genetic determinisms. In the model plant Arabidopsis thaliana, natural variation in nighttime transpiration was detected (21,22) and found to contribute significantly to total transpiration (23).…”
mentioning
confidence: 99%
“…First, night transpiration may lower leaf temperature by evaporative cooling, thereby decreasing carbon losses through dark respiration (42). Night water fluxes may otherwise have beneficial roles in nutrient transport (43) and O 2 supply to the xylem parenchyma (16,44). Incomplete stomatal closure at night may also accelerate photosynthesis resumption at sunrise (45), but this has not always been observed (46).…”
mentioning
confidence: 99%